EVALUASI METODE MENGHAFAL AL-QUR'AN DI RUMAH QUR’AN MUSLIM MADANI PARAKAN, BOLONG, KARANGANYAR - Roh Prehadi Santoso; Joko Subondo; Yetty Faridatul Ulfah (Institut Islam Mamba'ul 'Ulum Surakarta, 2022)
This study aims to (1) determine the evaluation of the input method for memorizing the Qur'an which includes the characteristics & abilities of the teacher and the ability of students to memorize, (2) know the evaluation of the process of memorizing the Qur'an which includes class division and the method applied, (3) know the evaluation of the output of the method of memorizing the Qur'an which includes the number and target of memorization. This study used an evaluation research approach and was carried out at the Muslim Madani Parakan Qur'an House by using data collection techniques in the form of observation, interviews and documentation. The results show that (1) the evaluation of the input data in the form of the background and characteristics of the teacher and the qualifications of the students was carried out less than optimally, so that the Qur'an House needed to revise the program (2) the evaluation of the data process in the form of dividing study groups and the method used was very good so that the house The Qur'an can continue the program (3) Evaluation of Data Output in the form of learning outcomes has not been maximized so that Rumah Qur'an needs to carry out policies to revise the program.The evaluator gave recommendations in the form of (1) Ummi method training for asatidzah (2) adding educators (3) classroom conditioning to be more disciplined.